1983
DOI: 10.1524/ract.1983.32.13.89
|View full text |Cite
|
Sign up to set email alerts
|

The Behavior of Actinides in the Environments

Abstract: A review of actinide behavior in the environment is presented with emphasis on chemical, physical, and biological factors that influence actinide mobility in ecosystems. Available data from terrestrial and fresh water ecosystems suggest that physical processes which result in the transport of soils and sediments dominate in the translational movement of plutonium and, as well, dominate in the transport of this element through lower trophic levels. Exceptions to that statement occur in arctic ecosystems and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 43 publications
4
10
0
Order By: Relevance
“…Stoker et al, 1981;Rogers et al, 2001). This is consistent with the expected geochemical behaviour of plutonium in the surface environment at near-neutral pH (Watters et al, 1983). (Note the name 'Acid Canyon' is derived from 'acid sewers' that received effluent from radiochemical facilities, although waters here were not strongly acidic.…”
Section: Contaminant Release History and Behavioursupporting
confidence: 83%
See 1 more Smart Citation
“…Stoker et al, 1981;Rogers et al, 2001). This is consistent with the expected geochemical behaviour of plutonium in the surface environment at near-neutral pH (Watters et al, 1983). (Note the name 'Acid Canyon' is derived from 'acid sewers' that received effluent from radiochemical facilities, although waters here were not strongly acidic.…”
Section: Contaminant Release History and Behavioursupporting
confidence: 83%
“…Average concentrations of plutonium in each reach are consistently higher in fine-grained sediment than in coarse-grained sediment, as expected from the geochemical behaviour of plutonium (Watters et al, 1983). When the data are divided into general age groups to reduce variability related to temporal trends in contaminant concentration, they indicate statistically significant relationships (p < 0·05) between plutonium concentrations and percentage clay or percentage silt and clay (Figure 8).…”
Section: Spatial Variations In Plutonium Concentrationsupporting
confidence: 58%
“…Over the last 50 years, nuclear research and development programs have resulted in releases of plutonium to both on-site and off-site locations. Most of this plutonium and other actinides are currently in soils where it is tightly bound to soil particles (Watters et al 1983), but these particles themselves are subject to redistribution. Research indicates that actinide redistribution is driven primarily by physical and biological processes associated with ecosystem dynamics, rather than by chemical processes.…”
Section: Research Objectivesmentioning
confidence: 99%
“…47 Evidence collected in investigations of plutonium and cesium-137 in Los Alamos Canyon have shown that stream sediments were the major reservoir of radioactivity from waste disposal activities of Los Alamos National Laboratory, and that runoff processes were moving the sediments downstream. 48 In a more general sense, radioecologists have indicated that "the distribution of transuranic elements from point sources at nuclear facilities typically produces decreasing concentrations with distance ,, 49 from the source.…”
Section: Related Researchmentioning
confidence: 99%